PEMANFAATAN INSTAGRAM SEBAGAI MEDIA EDUKASI TERHADAP PISO SUHUL GADING KHAS SUKU BATAK SIMALUNGUN - Irenia Jastisia; Annida Salsabila; Siti Afifah (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2022)
Every region in Indonesia has a cultural heritage. Piso suhul gading is a legacy of traditional weapons typical of the lowly tribes that are historically but rarely known to the public. Piso suhul gading was used by the royal family but now used as a complement to the custom. Therefore, qualitative descriptive research is being done by conducting interviews and observations on ceremonies using the piso suhul gading. This research aims to analyze the piso suhul gading and create media eduction through an Instagram aimed at introducing piso suhul gading as one of Indonesia's cultural heritage.